Partnering for economic development: How town-gown relations impact local economic development in small and medium cities - Massey, Jennifer (Canadian Journal of Higher Education, 2014)
Universities play an increasingly prominent role in shaping regional, social, and economic development. In Canada, however, spatial, economic, and social differences between universities and their host communities continue to challenge positive town–gown relationships and undermine the benefits associated with high concentrations of prospective young, “creative” graduates. The purpose of this article is to identify the factors that lead to positive town–gown relations and, subsequently, encourage graduate retention. Through this research, university and town administrators were found to play a key role in establishing a positive relationship between students and community members. Local employment opportunities were also found to help students build an experiential relationship with their localities and make them more likely to settle there after graduation.